Supernovas: una historia feminista de la ciencia ficción audiovisual - Méndez García, Carmen M. (Filanderas, 2020)
Supernovas: Una historia feminista de la ciencia ficción audiovisual, by Elisa McCausland y Diego Salgado, starts from an extremely ambitious premise: to summarize in four hundred and fifty pages more than a century of speculative fiction, not only in film, but also in television, illustration, comics or video games, in a global context.